(untitled) (African Human Mobility Review, 2025)
This study analyzes the experiences of urban refugee communities, more specifically, the challenges young South Sudanese refugees living in Kenya face. We divert from the comprehensive examination of refugees in camps to focus on urban youth amid Kenya’s refugee policy changes and the impact of the COVID-19 pandemic. With the support of South Sudanese community leaders, our study engaged 58 participants – 42 males and 16 females. Participants engaged in semi-structured discussions about food security and other daily challenges related to their urban refugee experience. This study draws on postcolonial feminist theory to contextualize the gender-specific dimensions of food insecurity, centering analysis on discussing historical power structures, migration patterns, urbanism theory, and geopolitical influences contributing to the experiences of South Sudanese urban refugee youth in Kenya. Study participants, irrespective of location, encountered corruption, limiting policies, and conflicting identity formation, with women specifically highlighting self-identity, dignity, and family as critical to supporting their resilience. Participants emphasized the impact of COVID-19 on community cohesion, particularly in shared meals. However, their agency was hindered by movement restrictions, invisible fences, or barriers exacerbated by unequal support and aid distribution. The research advocates for the formulation of clear African contextualized urban-based policies and migration systems that prioritize the needs of urban refugees, safeguarding their rights and upholding human dignity. Collaborative engagement with all stakeholders within local communities, especially youth refugees, is necessary to develop effective urban policies that promote stability, economic advancement, and social integration.